(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, it is highly mentioned that mature generation should not be consumers, but the creators and devotees of our modernized society, one of the main purpose of pedagogues and thoughts on conducting training on the process of personal development with students are described.